Dissipativity-Based Intermittent Fault Detection and Fault-Tolerant Control for Uncertain Switched Random Nonlinear Systems With Multiple Delays - Sun, Shaoxin; Zhang, Huaguang; Wang, Yingchun; Zhang, Juan (IEEE transactions on systems, man, and cybernetics. Systems, 2022)
The issue of fault detection (FD) and fault-tolerant control is developed for a switched random nonlinear system against multiple delays in this work. There also exist parameter uncertainties, exogenous disturbances, nonlinear functions as well as measurement noise in this model. This is one of the few tries to investigate the dissipativity issue and an design FD-based observer for the switched random system. Based on the dimensionally adjustable observer, the controller is designed to make this system noise-to-state exponentially mean-square stable. Then, these sufficient stability conditions can be earned by the piecewise Lyapunov function. Concurrently, this strict \left({\mathsf {Q}, \mathsf {S}, \mathsf {R}}\right)-{υ }- dissipativity performance, this elaborate H_{∞ } performance as well as this elaborate H_{} performance can be gained, separately. In addition, the merits and feasibility are presented via a numerical simulation and a practical example.